KAJIAN PENYIMPANAN DINGIN TERHADAP MUTU JAGUNG MANIS (Zea mays, saccarata) - Husni Halid; Handry Rawung; Ireine A. Longdong (Universitas Sam Ratulangi, 2015)
Abstract Sweet corn (Zea mays, saccarata) started and already recognized in Indonesia for a long time. Developing market demand for sweet corn continues to grow which trigger the sweet corn farming. Sweet corn distribution must be done as soon after it cultivated so that the sweet corn will taste sweet and it will decrease within 48 hours later (Rodja, 2009). Based on that statement, it is necessary to do research study titled cold storage of sweet corn. This study aims to determine the sugar content during storage, to calculate the weight of sweet corn during storage and observe the color change of sweet corn during storage. The results showed that the amount of decrease in sugar content during storage in the freezer is 0.1754% - 0.2842% and decreased levels of sugar stored at a temperature of space is 0.3859% - 0.4350%. Sugar level drops very visible in the storage room at a temperature of sweet corn, which decrease levels of sugar in the freezer is not as big as the decline of sweet corn were stored at a temperature of space.